Impregnation of various fiber tapes toward mechanical properties of dental fiber-reinforced composites - Sunarintyas, Siti; Irnawati, Dyah; Harsini, Harsini; Rinastiti, Margareta; Nuryono, Nuryono (Faculty of Dentistry, Universitas Gadjah Mada, 2023)
Synthetic dental fiber tape for fiber reinforcement (FRC) restoration is relatively costly and its availability is still limited in Indonesia, so natural dental fibers have been used as an alternative material. The aim of this study was to assess the effect of impregnation of various fiber tape toward the flexural strength and hardness of FRC. The materials used were natural Bombyx mori silk fibers (Indonesia), dental polyethylene tape (Construct Kerr, USA), dental Quartz tape (Quartz Splint UD, France), dental E-glass tape (Everstick TM, GC, Japan), silane coupling agent (Ultradent, Jordan), and composite resin (Denfil-Flow, USA). Five groups of samples consisted of FRC with various fiber tapes were prepared: unidirectional-silk, braided-silk, quartz, polyethylene, and E-glass. The five groups of FRC were tested to determine the flexural strength and hardness. The results were analyzed by one-way ANOVA, followed by LSD test. The results showed that the highest flexural strength was in the quartz group (496.84 ± 109.14 MPa), while the lowest was in the braided-silk group (139.39 ± 4.30 MPa). The highest hardness property was in the unidirectional-silk group (141.29 ± 25.17 VHN), while the lowest was in the braided-silk group (139.39 ± 4.30 VHN). The ANOVA showed that various fiber tapes significantly influenced the flexural strength and hardness of FRC (p < 0.05). The LSD showed that the unidirectional-silk, braided-silk, and polyethylene groups demonstrated no significant difference. The LSD for hardness showed that the unidirectional-silk group had a significant difference with the other groups (p < 0.05). It can be concluded that various fiber tapes influenced the flexural strength and hardness of FRC. Natural silk fibers showed comparable flexural strength and hardness with the other fiber tapes.